2010
DOI: 10.1074/jbc.m110.161547
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin Is Identical to Skin Fibroblast Elastase

Abstract: Although human skin fibroblast (HSF) elastase has been characterized as a membrane-bound metalloproteinase, little is known about its structure, amino acid sequence, and encoding gene. As there are similarities in the molecular weights and inhibitory profiles of HSF elastase and neprilysin (neutral endopeptidase 24.11 (NEP)), in this study we tested the hypothesis that they are identical using immunoprecipitation and transfection methods. An immunoprecipitation study demonstrated that HSF elastase activity co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…In addition to the peptidase activity of CD10, 10,11,31 it also has elastase activity that degrades elastic fibers. 32 One possibility is that the elastase activity of CD10 may facilitate tumor invasiveness, thereby degrading elastic fibers in the lung parenchyma. Additionally, Maguer-Satta et al suggested that upregulation of CD10 enzymatic activity may inhibit epithelial differentiation of stem cells into mature cells or maintain cancer stem cells by cleaving peptides for differentiating signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the peptidase activity of CD10, 10,11,31 it also has elastase activity that degrades elastic fibers. 32 One possibility is that the elastase activity of CD10 may facilitate tumor invasiveness, thereby degrading elastic fibers in the lung parenchyma. Additionally, Maguer-Satta et al suggested that upregulation of CD10 enzymatic activity may inhibit epithelial differentiation of stem cells into mature cells or maintain cancer stem cells by cleaving peptides for differentiating signaling.…”
Section: Discussionmentioning
confidence: 99%
“…NEP can degrade a wide variety of bioactive peptides, for example enkephalins [22], bradykinin [23], neurotensin, substance P [23], [24], CGRP [25], natriuretic peptide [26], fMet-Leu-Phe [27], endothelin [26], [28], and galanin [29]. We previously showed that NEP also has elastase activity and plays important roles during intrinsic and UV-induced skin aging [18]. We now report the role of NEP in regulating the hair cycle.…”
Section: Introductionmentioning
confidence: 82%
“…Previously we determined that NEP has an elastin degrading activity [18]. It wouldn’t be a surprise if elastin, which is a component of the ECM, has some involvement in hair cycle control, because the hair cycle is considered as a kind of process of tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also possesses elastase activity [48]. MME is a membrane-bound protein, however, as was recently shown, MME can be released to the microenvironment of cells in exosomes [49].…”
Section: Discussionmentioning
confidence: 99%